Continuum model of tendon pathology – where are we now?. Issue 4 (9th July 2013) - McCreesh, Karen; Lewis, Jeremy
Summary Chronic tendon pathology is a common and often disabling condition, the causes of which remain poorly understood. The continuum model of tendon pathology was proposed to provide a model for the staging of tendon pathology and to assist clinicians in managing this often complex condition (Br. J. Sports Med., 43, 2009, 409). The model presents clinical, histological and imaging evidence for the progression of tendon pathology as a three‐stage continuum: reactive tendinopathy, tendon disrepair and degenerative tendinopathy. It also provides clinical information to assist in identifying the stage of pathology, in addition to proposed treatment approaches for each stage. The usefulness of such a model is determined by its ability to incorporate and inform new and emerging research. This review examines the degree to which recent research supports or refutes the continuum model and proposes future directions for clinical and research application of the model.